Model Pertumbuhan Sepeda Motor Berdasarkan Produk Dosmetik Regional Bruto (PRDB) Perkapita (Studi Kasus Pulau Jawa) - Kresnanto, Nindyo Cahyo (Department of Civil Engineering, Diponegoro University, 2019)
The number and growth of vehicles, is a separate issue associated with sustainable transportation. In 2014, recorded vehicle election in Indonesia reached more than 448 vehicles per 1,000 people. And specifically, for motorcycles reach 365 vehicles per 1,000 people. The growth of motor vehicles is significantly influenced by economic growth (measured by Gross Domestic Product - RGDP). When compared with motor vehicle growth, it can be concluded that the high growth rate of motor vehicles at the end of this decade actually impact on the decrease of RGDP. To see the trend between economic growth represented by RGDP and the growth of motor vehicle (motorcycle) needs a model. Motor vehicle growth model in Java can be approached with Gompertz function. This function is a negative exponential function with asymptote used is the highest value of motor vehicle ownership in DKI Jakarta Province is 1,299 motorcycles per 1,000 people.